Multiperiod Consumption and Investment Behavior with Convex Transactions Costs - Constantinides, George M. (Management Science, 1979)
The effect of convex transactions costs on consumers' derived utility functions and on optimal consumption and investment decisions is examined in a general multiperiod framework. The extent to which multiperiod consumption-investment behavior and capital market equilibrium may be studied in a single period framework is discussed. Optimal investment policy, in terms of a region of no transactions, is shown to be of a particularly simple form.